Web Conference Internet Traffic Analysis during Study-from-Home Period: Case in Sampoerna University - Muhammad Agni Catur Bhakti; Wandy Wandy (Indonesian Journal of Computing, Engineering, and Design (IJoCED), 2020)
Web conference feature embedded in Learning Management System (LMS) has been implemented in Sampoerna University (SU) to support mandatory Teaching-and-Learning from home activities during early stage of Covid-19 spreading period in Jakarta. The use of technologies and Internet connection to support these academic activities became very essential. The objec-tive of this research is to analyze internet speed and quota con-sumptions to meet the web conference requirements. Lecturers and students need sufficient Internet quota, stable Internet connection with proper speed, either using wired or wireless connection, in prepaid or postpaid subscriptions for smooth online learning. This research was an exploratory and quantitative research with surveys using non-probability with identified voluntary response sampling. The results showed that web conferences using BigBlueButton for audio-call, text-based chat, and rarely updated presenter shared-screen consumed only 3.11% of average students’ Internet connection speed, while the quota consumptions for 3 Credit Points Course session were 129.15 MB (Megabyte) per session, and for 4 Credit Points Course session were 140.2 MB per session. It was concluded that students are supposed to experience no or less delay during web conferences, and still have plenty of Internet bandwidth that can be utilized to support Study-from-Home activities.